Strategy and tactics of the Salvadoran FMLN guerrillas: last battle of the Cold War, blueprint for future conflicts - Moroni Bracamonte, José Angel (Praeger, 1995)
"Excellent description and analysis"--Handbook of Latin American Studies, v. 57